Pengaruh Bauran Pemasaran terhadap Loyalitas Konsumen pada Usaha Petik Apel Mandiri di Kecamatan Bumiaji Malang - Dona Wahyuning Laily; Aprilia Tri Wulandari; Hamidah Hendrarini (Universitas Batanghari Jambi, 2023)
The purpose of this study was to identify the characteristics of consumers when visiting Mandiri Apple Pickers in Bumiaji District, Malang, to analyze the effect of the marketing mix on consumer loyalty in independent apple picking businesses in Bumiaji District, Malang, to identify the obstacles and efforts faced by Mandiri Apple Picking businesses in increase consumer loyalty. The population in this study were all customers who visited the independent apple picking business in Bumiaji District, Malang. The researcher determines that the number of respondents in the research is 100 respondents. The results of this study are that the characteristics of Mandiri Apple Picking consumers are that the majority are female by 66%, while for men it is 34%, then for the age of the majority of consumers aged 31-35 it is 32%. With the last education, the majority of high school is 43% and the majority of consumers work as housewives 22% and other jobs 27%. Based on the results of the research results of multiple linear regression analysis Test (F) there is a simultaneous or joint effect between the independent variable (X) on the variable (Y). On the results of the (Partial) T-Test that has been carried out from 7 Independent Variables of the marketing mix, there are 6 independent variables that have a partial effect on consumer loyalty, while for the independent variables that have no effect on consumer loyalty, namely Promotion. From the results of research that has been done constraints and efforts to increase consumer loyalty include: elements of the Marketing Mix, namely promotions that are less effective at Mandiri Apple Picks, product offerings that are less attractive and varied, and many competitors doing the same business.